2012 5th European DSP Education and Research Conference (EDERC) 2012
DOI: 10.1109/ederc.2012.6532240
|View full text |Cite
|
Sign up to set email alerts
|

Wireless system for remote monitoring of atrial fibrillation

Abstract: In this paper is described the design and implementation of a wireless atrial fibrillation monitoring system, for realtime remote patient monitoring in a limited area, using wireless sensor networks (WSN). The proposed system consists of a lightweight and low power wireless ECG acquisition and processing device, connected to a central monitoring station through WSN. The device is able to detect the paroxysmal atrial fibrillation episodes and transmits alerts to the central monitoring station. The system can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…The WAPU sends the packet through the router to internet-based web server. This data is available for hospital and caregiver [71]. In a similar study in [60] reported for one patient, which also enables feature of emergency alert and support.…”
Section: Home and Healthcarementioning
confidence: 71%
“…The WAPU sends the packet through the router to internet-based web server. This data is available for hospital and caregiver [71]. In a similar study in [60] reported for one patient, which also enables feature of emergency alert and support.…”
Section: Home and Healthcarementioning
confidence: 71%
“…In [20] they proposed a very interesting system but no adjustments are made to compensate the variations of the user's metabolism. In [6] they understood the desirable necessity of a continuous heart rate monitoring and the target to be not bound by the proximity to the radio base station.…”
Section: Related Workmentioning
confidence: 99%
“…WE can monitor the body status by devices that measure heart or brain activity, blood pressure, body temperature, and other body functions [26]. Just to present a couple of examples; the realization of wireless oxygen saturation and heart rate system for patient monitoring [27], a scheme for monitoring the patient's temperature, heartbeat, and pressure [28], and a wearable health system for non-invasive and wireless monitoring of physiological signals [29] have been introduced, which opens up a realm of possibilities when addressing the issues within the healthcare sector for coping with chronic diseases and an aging population.…”
Section: We In Healthcarementioning
confidence: 99%